Rise of the Eagle Owl population due to rat-rich refuse dump sites and fall when closing them: a large-scale long-term “supplementary feeding experiment” - Tornberg, Risto; Huhtala, Kauko; Mikkola, Heimo; Tolvanen, Jere; Valkama, Jari; Korpimäki, Erkki (BirdLife Finland, 2026)
Food-supplementation experiments conducted on terrestrial vertebrates have usually shown the importance of food as an agent in increasing reproductive success. However, to date, the number of large-scale food supplementation experiments carried out on top predators has been limited. The Eurasian Eagle Owl (Bubo bubo) is the largest nocturnal avian predator in the boreal and temperate regions of Eurasia. Here, we study the diet composition and breeding success of this top predator in relation to the location and distance to rubbish dumps, which sustain large numbers of brown rats Rattus norvegicus, one of the main prey items for owls. The number of these rubbish dumps (hereafter dumps) increased in Finland during the period between the 1960s and the 1990s, whereafter their number was steeply reduced, leading to a remarkable decline in rat populations. A similar trend in the Eagle Owl population largely followed this development, raising the question of whether this country-wide "supplementary feeding experiment" was behind this phenomenon. The proportion of rats in the diet of the owls was high, on average, 70% of prey items near the dumps decreasing to around 10–15% at a 6–7 km distance from the dumps. Correspondingly, the number of 3–4-week-old offspring declined in relation to the distance from the dump, so that 0.5 less chicks were recorded at a distance of 10 km from the dump. During the study, the overall density of nests near the dumps was 2.7 times higher than those recorded further away. The availability of extra food material within the dumps (and rats therein) probably induced an increase in the Finnish Eagle Owl population, which saw a decline after dumps were closed.